Discourse and breastfeeding practice in urban communities in Indonesia: A Foucauldian perspective - Mulyaningsih, Hetti; Suyanto, Bagong; Sugihartati, Rahma (Jurnal Studi Komunikasi, 2020)
Breastfeeding coverage in Indonesia is under government target. Several works of literature illustrate that mothers in Indonesia face three classic problems. First, inadequate regulation to protect breastfeeding practices, second, the massive promotion of infant formula and breast-milk substitutes, and third, discrepancies in health services. This article aimed to explore the experiences of breastfeeding mothers and to relate it to broader discourse. The study was conducted in two metropolitan cities in Indonesia, Jakarta, and Surabaya. Both locations were chosen because the two cities share similar characteristics, namely urban communities with dense, heterogeneous populations and rapid changes. The study is a critical discourse analysis using the Foucauldian perspective to help examine the discourse and the social practices of breastfeeding. Data were collected with semi-structured interviews on 36 research subjects. The results confirmed that all subjects recognised the benefits of breastfeeding discourse. However, the practice of infant feeding was not always related to health recommendations. The study also found three issues concerning breastfeeding practice, namely: discourse on breastmilk and biopower, failed mothers, and mothers’ negotiation. The discourse on breastfeeding is recognised as a biopower discourse which is an extension of affected mothers’ identities. Mothers who fail to breastfeed feel guilt, frustration and shame. They tried to negotiate this condition by asking health workers for help and arguing that the identity of the mother is not only influenced by the practice of breastfeeding. Therefore, a constructive biopower discourse is needed to implement breastfeeding practices and discourses to normalise breastfeeding practices.